2015
DOI: 10.1038/srep08156
|View full text |Cite
|
Sign up to set email alerts
|

Social priming enhances interpersonal synchronization and feeling of connectedness towards schizophrenia patients

Abstract: What leads healthy individuals to abnormal feelings of contact with schizophrenia patients remains obscure. Despite recent findings that human bonding is an interactive process influenced by coordination dynamics, the spatiotemporal organization of the bodily movements of schizophrenia patients when interacting with other people is poorly understood. Interpersonal motor coordination between dyads of patients (n = 45) or healthy controls (n = 45), and synchronization partners (n = 90), was assessed with a hand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Many studies have found indicators of persistent problems of nonverbal communication in patients with schizophrenia, such as reduced facial expression [ 30 33 ]. Their deficits in social skills have been analyzed using observer-based rating scales [ 17 , 34 ], and more recently, with objective measures of movement [ 21 , 22 , 35 38 ]. Nonverbal behavior in patients with schizophrenia can be assessed objectively using ordinary video recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found indicators of persistent problems of nonverbal communication in patients with schizophrenia, such as reduced facial expression [ 30 33 ]. Their deficits in social skills have been analyzed using observer-based rating scales [ 17 , 34 ], and more recently, with objective measures of movement [ 21 , 22 , 35 38 ]. Nonverbal behavior in patients with schizophrenia can be assessed objectively using ordinary video recordings.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination dynamics approach offers experimental paradigms for scrutinizing specific aspects of bodily connectedness, which may help to assess defining characteristics of autism, such as poor social initiative and reciprocity. To enhance the sensitivity of the proposed empirical methods additional modulations of the social setting may be applied, such as implicit social priming (Raffard et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…In TD individuals, matching and synchronization of bodily movements are associated with (psychological) characteristics of the interactants and the quality of their relationship, such as self-esteem (Lumsden et al, 2014), pro-social attitudes (Lumsden et al, 2012), physical attractiveness (Zhao et al, 2015), rapport (Hove and Risen, 2009; Raffard et al, 2015), and perceived social difference (Miles et al, 2011). Moreover, moving in synchrony fosters cooperative abilities (Wiltermuth and Heath, 2009; Valdesolo et al, 2010).…”
Section: Bodily Connectedness As Marker For Social Abilitiesmentioning
confidence: 99%
“…24, 51 Consequently, interaction with artificial agents could become a part of future therapeutic protocols that would allow for real-time monitoring of therapy progress.…”
Section: Discussionmentioning
confidence: 99%